Justification of the Courant-Friedrichs conjecture for the problem about flow around a wedge - Blokhin, A. M. (Aleksandr Mikhaĭlovich); Tkachev, D. L.; Mishchenko, E. V. (Evgenii͡a Vasilʹevna) (Mathematics research developments series., 2013)
The classical problem about a steady-state supersonic flow of an inviscid non-heat-conductive gas around an infinite plane wedge under the assumption that the angle at the vertex of the wedge is less than some limit value is considered. The gas is supposed to be in the state of thermodynamical equilibrium and admits the existence of a state equation. As is well-known, the problem has two discontinuous solutions, one of which is associated with a strong shock wave (the gas velocity behind the shock wave is less than the sound speed) and the second one corresponds to the weak shock wave (the gas.